Workplace interventions for Finnish nurses: a retrospective document analysis of disciplinary decisions related to substance use - Luurila, Katrimaija; Kangasniemi, Mari; Hult, Marja; Häggman-Laitila, Arja (SAGE PUBLICATIONS LTD, 2026)
Aim: The study aimed to describe the workplace interventions for registered nurses (RNs) with substance use disorder (SUD) related violations leading to disciplinary actions.
Methods: A retrospective document analysis of disciplinary decisions related to RNs with SUD (N = 171) from a Finnish regulatory authority. The data were analyzed using descriptive statistics and qualitative methods.
Results: Substance abuse at the workplace involved intervention actions by a nurse leader and employer with work ability assessment and measures, legislation-based measures for hearing the worker, investigation and handling. Substance abuse services and occupational health services were involved in more than half of incidents. In most of the cases, the RN's contract terminated.
Conclusions: Further research about the interventions and supervision of healthcare workers with SUD could help clarify protocols and develop measures for the early detection at work places.